2021
DOI: 10.1111/ntwe.12207
|View full text |Cite
|
Sign up to set email alerts
|

Performance management technologies and trade union responses: A case study from banking

Abstract: Literature in the Performance Management (PM) field champions a shift to more continual forms of worker assessment. Advances in data analytic technologies are claimed to support such developments. However, critical literature finds that PM technologies induce malign consequences for workers and that unions should seek to organise an alternative agenda challenging employers. Based on findings from an action research project in retail and operations banking, the paper considers whether organising enables unions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This focus has allowed us to shed light on “in-between spaces” and on individual workers' strategies of resistance and negotiation, as seen in the empirical section. Furthermore, such action research allows us to explore collective and trade union strategies in reacting to the digitalization of banking work and in exercising collective voice by potentially undertaking new battles and an alternative agenda for collective bargaining (Murphy and Cullinane, 2021 ; Kornelakis et al, 2022 ). This is a crucial and evolving issue that will be the subject of subsequent analysis and goes beyond the primary objective of this article, that is to investigate the role of new technologies in the service triangle in retail banking.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This focus has allowed us to shed light on “in-between spaces” and on individual workers' strategies of resistance and negotiation, as seen in the empirical section. Furthermore, such action research allows us to explore collective and trade union strategies in reacting to the digitalization of banking work and in exercising collective voice by potentially undertaking new battles and an alternative agenda for collective bargaining (Murphy and Cullinane, 2021 ; Kornelakis et al, 2022 ). This is a crucial and evolving issue that will be the subject of subsequent analysis and goes beyond the primary objective of this article, that is to investigate the role of new technologies in the service triangle in retail banking.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Growing managerialization, globalization and increasing competition with actors other than banks have markedly changed employment practices and the way work is traditionally performed in the banking industry: studies from different countries have shown that a process of segmentation of work organization, accompanied by the narrowing of task variation, work intensification, and Taylorization, especially for customer-facing jobs, together with increased managerial control and the strengthening of sales culture, is proven to cause worrying levels of stress, a sense of alienation and hard work identity, hence characterizing an occupation that was traditionally associated with high prestige, meaningful work and advanced technical knowledge and skills (Regini et al, 1999;McCabe, 2007McCabe, , 2009Gond et al, 2014;Kipping and Westerhuis, 2014;du Plessis and Just, 2022). Technology in this long-standing process of bank work change seems to reduce employees to the status of machines that must passively fulfill the tasks assigned to them and whose performance is measured individually through a combination of innovative control systems and older disciplinary forms of management (Regini et al, 1999;McCabe, 2007), thus opening up new challenges for trade union organizing (Murphy and Cullinane, 2021;Kornelakis et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Others report jobs becoming increasingly standardised, with reduced discretion and greater use of targets (Laaser, 2016; Perez and Martin, 2018). Work intensification is a common theme (Dølvik et al, 2020; NFU, 2018; Perez and Martin, 2018), alongside concerns surrounding the effects of enhanced forms of digital monitoring and surveillance (Lockwood, 2018; Murphy and Cullinane, 2021).…”
Section: Digitalisation In Bankingmentioning
confidence: 99%